2008
DOI: 10.2166/wst.2008.185
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of industrial wastewater for the irrigation of ornamental plants

Abstract: This paper describes the results of experimental activities carried out for verifying the possibility of reusing reclaimed wastewater originated from textile (70%) and domestic (30%) activities for the irrigation of container-grown ornamental shrubs. Aspects that concern the refinery treatment of reclaimed wastewater and the effect of irrigation on some ornamental plant species were investigated. An experimental site consisting of a refinery treatment pilot plant (filtration and disinfection) and an agronomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…To minimize crop loss, it is necessary to identify new irrigation management strategies, such as increased leaching, to maintain high and constant substrate humidity (Bañón et al, 2011), or to use salt-tolerant plants and develop salt-tolerant crops through breeding programmes. One solution to improving the agronomic quality of the reused water could be to blend it with well water (Chaiprapat and Sdoodee, 2007;Gori et al, 2008;Bañón et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize crop loss, it is necessary to identify new irrigation management strategies, such as increased leaching, to maintain high and constant substrate humidity (Bañón et al, 2011), or to use salt-tolerant plants and develop salt-tolerant crops through breeding programmes. One solution to improving the agronomic quality of the reused water could be to blend it with well water (Chaiprapat and Sdoodee, 2007;Gori et al, 2008;Bañón et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…185/2003) for RWW to be reused for irrigation; † assessing the effect of RWW on some ornamental plant species representative of the local nursery production Gori et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning industrial wastewaters, the treated effluent was suitable for the irrigation of ornamental plants but the use of drip irrigation should be suggested in order to avoid a decrease in the quality of the plants produced due to tip and edge burn of leaves. Moreover, because of the saltsensibility of numerous plants, the use of a tertiary effluent with such water quality can always be recommended for short periods (Gori et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For this, determination of the organic load in the studied wastewaters was performed through calculation of BOD5 and COD. Gori et al (2008) [46] conducted experiments to verify the possibility of reusing industrial wastewater of comparable quality to that used in this study (originated from textile (70%) and domestic (30%) activities) for the irrigation of ornamental shrubs. They found that some of them (Buxus and Pistacia) showed no signs of toxicity, while others (Viburnum and Photinia) showed greater sensitivity especially during sprinkle irrigation.…”
Section: +mentioning
confidence: 99%